2019
DOI: 10.1007/s10354-019-0689-8
|View full text |Cite
|
Sign up to set email alerts
|

The status of health economic evaluation within decision making in Austria

Abstract: Summary Background Given limited resources compared to the demand for them, spending resources efficiently is important. Key methods applied for supporting efficient resource allocation are health economic evaluations. Methods Based on secondary literature, we analyze international challenges for using two types of economic evaluations—cost-effectiveness analysis and cost-utility analysis—in reimbursement decisions and reflect on them for the Austrian case.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…Our protocol for evaluating the eE Program describes a ‘slow science’ research design [ 21 ], designed to overcome this and other barriers to the use of economic evaluation listed in previous reports [ 17 , 34 41 ]. As far as the authors are aware, no previous designs have sought to document and tease apart the process of interaction and the relational aspects of engagement of an embedded economist with health service managers.…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol for evaluating the eE Program describes a ‘slow science’ research design [ 21 ], designed to overcome this and other barriers to the use of economic evaluation listed in previous reports [ 17 , 34 41 ]. As far as the authors are aware, no previous designs have sought to document and tease apart the process of interaction and the relational aspects of engagement of an embedded economist with health service managers.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies around the world have assessed challenges in using and conducting economic evaluations [ 16 , 24 , 25 , 32 ]. Luz et al [ 16 ] investigated the perceived challenges of conducting, using and reporting economic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This also echoes findings in other studies [ 7 , 16 , 25 ]. Challenges related to decision-makers’ support, confidence and understanding of the use of economic evaluations have also been addressed in other studies [ 24 , 25 , 32 ]. A study conducted by Roseboom et al [ 25 ] found that decision-makers have some difficulties in interpreting economic evaluation outcomes, including QALYs, and in dealing with issues around the transferability of data across countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic evaluation area in healthcare joins the economy rationalization to decision making in this sector (Zechmeister-Koss et al, 2019). In Brazil and around the world, health systems and their managers are facing challenges to offer quality health care to the population considering the available resources (Brazil, 2009;Zechmeister-Koss et al, 2019).…”
Section: Introductionmentioning
confidence: 99%